The Brain Jogging Training: Solution for Increasing Playing Skill in Field Hockey Athlete - Budiman, Ali; Pasaribu, Ahmad Muchlisin Natas (Program Studi Pendidikan Kepelatihan Olahraga Fakultas Ilmu Pendidikan Universitas Bhayangkara Jakarta Raya, 2023)
The brain jogging training method is a training method that further sharpens the cognitive abilities of an athlete. The purpose of this study was to find out how the impact this brain jogging exercise had on the playing skills of field hockey athletes. The research method used is an experimental research method with a research design in the form of a one group pre-test post-test design. A total of 23 STKIP Pasundan field hockey athletes were used as research samples. The research treatment was carried out for 8 weeks excluding the pre-test and post- test. The research instrument used is the Game Performance Assessment Instrument (GPAI). The results showed that the increase in playing skills was 0.2 (2%), and showed that there was a significant effect of the application of brain jogging exercises on the playing skills of field hockey athletes (sig. 0.000). So that it can be concluded that the brain jogging training method is very feasible to be applied to the training process of field hockey athletes, especially to improve their playing skills.